2015
DOI: 10.4103/0976-0105.145773
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about the availability of the pharmacist in the Nuclear Medicine Department: A questionnaire-based study among health-care professionals

Abstract: Objective:The objective of this study was to analyze the knowledge about the availability of the pharmacist in the nuclear medicine department among health-care professionals through a prospective cohort study.Methods:A total of 741 health-care professionals participated in the study by answering 10 simple questions about the role of the pharmacist in the nuclear medicine department and the availability of pharmacist in the nuclear medicine department. An online questionnaire system was used to conduct the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…[24,25] In this study, pharmacists' knowledge regarding radiopharmaceutical products is inferior, as reported by a previous study. (7) The highest knowledge with commonly used radioactive drug-like 131-Sodium Iodide 201 TI-Thaluim solution might be different from radioactive drugs used in an earlier study. [16] Most of the responders used drug information resources (e.g., PubMed) and scientific literature from the internet on nuclear pharmacy, which shows that the pharmacists were more familiar with drug information resources and online resources.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…[24,25] In this study, pharmacists' knowledge regarding radiopharmaceutical products is inferior, as reported by a previous study. (7) The highest knowledge with commonly used radioactive drug-like 131-Sodium Iodide 201 TI-Thaluim solution might be different from radioactive drugs used in an earlier study. [16] Most of the responders used drug information resources (e.g., PubMed) and scientific literature from the internet on nuclear pharmacy, which shows that the pharmacists were more familiar with drug information resources and online resources.…”
Section: Discussionmentioning
confidence: 90%
“…Another study showed that the availability of nuclear pharmacy at healthcare organizations is only 16%. [7] In this study, pharmacist's knowledge of nuclear medicine was affected by various factors, such as location. The southern region scored the lowest about knowledge of nuclear pharmacy, which may be because the pharmacists were not properly working in nuclear medicine or did not provide nuclear pharmacy services at their healthcare institutions.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…[34] Moreover, nuclear pharmacists provide clinical activities to the patients. [29][30][31]33,[35][36][37] Despite all the previous positive answers, the majority of the responders of nuclear pharmacy practice did not participate in this study. Thus, our results showed no difference between the practice of nuclear pharmacy services because of the small sample size.…”
Section: Discussionmentioning
confidence: 99%